Maternal emulsifier consumption alters the offspring early-life microbiota and goblet cell function leading to long-lasting diseases susceptibility - Clara Delaroque; Héloïse Rytter; Erica Bonazzi; Marine Huillet; Sandrine Ellero-Simatos; Eva Chatonnat; Fuhua Hao; Andrew Patterson; Benoit Chassaing (Nature Communications)
Abstract Early-life acquisition of microbiota and, consequently, immune system development, both lastingly impacts health. Accordingly, we hypothesized that disturbing the microbiota of lactating mothers via consumption of dietary emulsifiers might alter the microbiota, and perhaps the immune system, of their offspring, thereby increasing susceptibility to microbiota-mediated diseases, including colitis and metabolic syndrome. Here we report that, in mice, maternal consumption of carboxymethylcellulose and polysorbate-80 resulted in transient alterations in offspring microbiotas that were necessary and sufficient to increase proneness to colitis and metabolic syndrome in young adulthood. Offspring microbiome alterations induced by maternal emulsifier consumption resulted in elevated levels of pro-inflammatory flagellin, bacterial encroachment, and premature closure of goblet cell associated antigens passages (GAPs). The latter event was linked to phenotypic outcome in that pharmacologically preventing GAP closure eliminated the detrimental of maternal emulsifier consumption. Collectively, these results illustrate the potential of dietary emulsifiers to drive transgenerational microbiota alteration and, consequently, hastened immune development that increases susceptibility to inflammatory diseases.